Information and communication technologies in tourism 2013 : proceedings of the International Conference in Innsbruck, Austria, January 22-25, 2013 - International Conference on Information Communication Technologies in Health 2013; Cantoni, Lorenzo; Xiang, Zheng (Berlin : Springer, 2013)
The papers presented in this volume advance the state of the art in social media and Web 2.0, electronic tourism marketing, web site and search engine optimization, technology adoption and diffusion, online communities, tourism management and decision support, eLearning, mobile technologies and applications in tourism, recommender systems, e-intermediaries and networks in tourism, customer research in e-tourism and user generated content. The volume collects research papers of prominent scholars from around the world with a disciplinary background in the fields of social or computer sciences. The book covers the most significant topics within the study field of electronic tourism and addresses both, academics and practitioners interested in the latest advances in the electronic travel and tourism domain.
Conceptualizing Context in an Intelligent Mobile Environment in Travel and Tourism / Carlos Lamsfus, Zheng Xiang -- Discovering Functional Requirements and Usability Problems for a Mobile Tourism Guide through Context-Based Log Analysis / Elena Not, Adriano Venturini -- Engineering Augmented Tourism Experiences / Zornitza Yovcheva, Dimitrios Buhalis -- Exploring the Role of In-Trip Applications for Sustainable Tourism: Expert Perspectives / Mareba M. Scott, Andrew J. Frew -- The Adoption of Smartphone Applications by Airlines / Yuzhu Liu, Rob Law -- Transforming the Travel Experience: The Use of Smartphones for Travel / Dan Wang -- Time-of-Arrival Estimation in Mobile Tour Guides / Arthur Pitman, Josef Bernhart -- When Cell Phones Become Travel Buddies: Social Attribution to Mobile Phones in Travel / Iis Tussyadiah -- Building Destination Image through Online Opinionated Discourses. The Case of Swiss Mountain Destinations / Silvia De Ascaniis, Nicole Bischof -- Drivers and Benefits of Analysing DMOs' eWOM Activities / Elena Marchiori, Pauline Milwood. E-destinations: Global Best Practice in Tourism Technologies and Applications / Dimitrios Buhalis, Ramona Wagner -- Integer Programming Formulation of Finding Cheapest Ticket Combination over Multiple Tourist Attractions / Moonyoung Kang -- Grassroots Branding with Twitter: Amazing Florida / Svetlana Stepchenkova, Andrei Kirilenko -- Multi-Dimensional Data Modelling for a Tourism Destination Data Warehouse / Wolfram Höpken, Matthias Fuchs, Gerhard Höll -- What did they say about us? Message Cues and Destination Reputation in Social Media / Elena Marchioria, Lorenzo Cantonib -- Tourism Destinations as Digital Business Ecosystems / Rodolfo Baggio, Giacomo Del Chiappa -- Attracting User Social Media Engagement: A Study of Three Budget Airlines Facebook Pages / Rosanna Leung, Markus Schuckert, Emmy Yeung -- Backpacking, Social Media, and Crises: A Discussion of Online Social Convergence / Cody Morris Paris -- Destination Expertise in Online Travel Communities / Martin Hochmeister, Ulrike Gretzel -- Personal Profile Information as Cues of Credibility in Online Travel Reviews / Hee Lye Park, Zheng Xiang, Bharath Josiam. Social Media Strategy and Capacity for Consumer Co-Creation Among Destination Marketing Organizations / Iis Tussyadiah, Florian Zach -- Towards an Understanding of Online Travellers' Acceptance of Consumer-Generated Media for Travel Planning: Integrating Technology Acceptance and Source Credibility Factors / Julian K. Ayeh, Norman Au, Rob Law -- A Citation Analysis of Enter Proceedings in 2005-2012 / Liang Wang, Sammy Guo, Daniel Leung, Rob Law -- Analysing the Penetration of Web 2.0 in Different Tourism Sectors From 2008 to 2012 / Miriam Scaglione, Roland Schegg -- High Tech for High Touch Experiences: A Case Study From the Hospitality Industry / Barbara Neuhofer, Dimitrios Buhalis -- Interdisciplinary Research on Information Science and Tourism / Nao Li, Dimitrios Buhalis, Lingyun Zhang -- Sightsmap: Crowd-Sourced Popularity of the World Places / Tanel Tammet, Ago Luberg, Priit Järv -- Sources of Customer Role Learning During Self-Service Technology Encounters / Petranka Kelly, Jennifer Lawlor. The Development of an Evaluation Framework for Determining the Economic Value and Effectiveness of Internet Room Diagramming Solutions / Kuan-Wen Lin, Andrew J. Frew, Joe Goldblatt -- Examining Perceptions of the Importance of Travel Websites' Value-Added Services: Age, Gender, and Travel Motivations / Juho Pesonen -- Online Motor Magazines: An Opportunity for eTourism? / Giulio Lizzi, Samuele Prosino -- Same, Same but Different. How Pictures Influence Emotional Responses of Users with Different Web Search Behaviours / Gerhard Mariarcher, Amata Ring -- The Customers' Perspective on Presenting Visual Hotel Information Online / Marcel Grüter, Vanessa Schneider -- Virtual Experience on Hotel Websites: A Web Analysis / Marcel Grüter, Vanessa Schneider -- What Matters to The Industry? An Evaluation Framework for the Adoptability of Online Tourism Distribution Platforms / Sofia Reino, Aurkene Alzua-Sorzabal -- A Tagging Recommender Service for Mobile Terminals / Fernando A. Mikic Fonte, Marta Rey López -- Ontology-Based Identification of Music for Places / Marius Kaminskas, Ignacio Fernández-Tobías. Semantic Schedules for Dynamic Route Planning / Srdan Piljic, Wilhelm Loibl -- Unplanned Behaviour of Exhibition Attendees and the Booth Recommender System: The Goal Framing Theory Perspective / Namho Chung, Chulmo Koo, Jae Kyeong Kim -- Adopting Network Multimedia Systems in Interactive Digital Television: A Strategic Method Towards Enhancing Tourism Relationship Marketing / George Mastorakis, Nikolaos Trihas -- Hybrid User Modelling Algorithms for Tourism Providers / Isabel Torre, Maria Teresa Linaza -- Identifying Tourist Dispersion in Austria by Digital Footprints / Wolfgang Koerbitz, Irem Önder -- Personal Data and User Modelling in Tourism / Ioannis Stavrakantonakis -- Between Online and Offline Channels: Internship Information Search by Tourism and Hotel Management College Students / Lawrence Hoc Nang Fong, Hee Andy Lee -- Online Channel Use and Destination Advertising Response / Jason L. Stienmetz, Daniel R. Fesenmaier -- A Methodology to Collect Information on Future Hotel Prices Using Internet Distribution Systems / Aurkena Alzua-Sorzabal -- Distribution Channels and Management in the Swiss Hotel Sector / Roland Schegg, Brigitte Stangl, Michael Fux.
Περιέχει βιβλιογραφικές παραπομπές.
Keywords: Τουρισμός -- Επεξεργασία δεδομένων.; Τουρισμός -- Συνέδρια.; Tourism -- Information technology; Tourism -- Data processing; Τουρισμός -- Πληροφορική.; Tourism -- Computer network resources; Tourisme -- Congress